2009
DOI: 10.2747/0272-3646.30.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Entrainment Potential in Modified Alluvial Streams: Implications for Re-Mobilization of Stored In-Channel Sediment

Abstract: Alteration of sediment dynamics is a common effect of human disturbance in fluvial systems. The longevity of human-induced changes and the implications of altered sediment dynamics for system-wide responses to disturbance are not entirely understood. In this study, I calculated sediment entrainment potential (τ bf /τ cr ) for the D 50 particle measured for 34 reaches located in three alluvial streams currently adjusting to historic disturbance, including channelization and land clearance, that have large in-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ratios of actual hydraulic values in each section to critical values for the range of sizes found were calculated (Fig. 6) 35,59 .…”
Section: Methodsmentioning
confidence: 99%
“…Ratios of actual hydraulic values in each section to critical values for the range of sizes found were calculated (Fig. 6) 35,59 .…”
Section: Methodsmentioning
confidence: 99%
“…Another example where streams do not follow the classic CEM progression is seen in small tributaries in the Southeast USA. Davis (, ) found that homogenous bank materials promote simultaneous widening and incision as the primary form of adjustment within the same watershed. Rhoads and Urban () and Urban and Rhoads () revealed that channelization did not produce significant bed‐level changes along the Embarras River, Illinois, which they attributed to low stream power and resistant bed materials.…”
Section: An Overview Of Classic Channel Evolution Modelsmentioning
confidence: 99%
“…Alluvial bench occurrence has been related to sediment transport-limited conditions (Changxing et al, 1999;Schumm, 2005), the maintenance of stream equilibrium-accreting during drought-dominated periods to contract the channel and eroding during flood-dominated periods to widen the channel (Erskine and Livingstone, 1999), sediment dynamics associated with specific flow stages (mean annual Q or bankfull Q, for example) (Osterkamp and Hupp, 1984), or localized hydraulic changes that initiate deposition (Vietz et al, 2011). While not often the focus of many geomorphic studies in the past, benches have been documented in regions varying from subarctic (Hickin, 1979) to arid (Marren et al, 2006) and in a variety of geologic settings (Webb et al, 2002;Davis, 2009). Benches serve as finescale ecotones bridging aquatic and riparian zones, provide habitat for many species, and can be highly effective carbon and nitrogen sinks (Powell and Bouchard, 2010).…”
Section: Introductionmentioning
confidence: 97%